Reversal of Hofmeister ordering for pairing of NH4(+) vs alkylated ammonium cations with halide anions in water - Heyda, Jan; Lund, Mikael; Oncák, Milan; Slavícek, Petr; Jungwirth, Pavel (The journal of physical chemistry. B, 2010)
Pairing of halide anions with ammonium, as well as with trialkylated and tetraalkylated ammonium cations in water, is investigated by molecular dynamics simulations, which are verified by ab initio calculations and experimental excess chemical potentials. We find that ammonium prefers to pair with smaller halides over the larger ones, while the order is reversed for tetraalkylated ammonium cations. Trialkylated ammonium cations exhibit an intermediate behavior, with the acidic hydrogen preferring smaller anions and alkyl chains interacting attractively with larger halides. This Hofmeister reversal of anionic ordering upon tetraalkylation of the ammonium cation is robustly predicted by both nonpolarizable and polarizable force fields and supported by experimental evidence.
Keywords: kvartérní amoniové sloučeniny; molekulární konformace; Halogens; Molecular Conformation; simulace molekulární dynamiky; termodynamika; halogeny; Quaternary Ammonium Compounds; alkylace; Alkylation; Thermodynamics; Water; Substrate Specificity; Molecular Dynamics Simulation; substrátová specifita; voda